Health related quality of life of women garment factory workers: Association with their food security and nutritional status (Journal of the Bangladesh Agricultural University, 2020)
Health related quality of life (HRQOL) is an individual’s or a group’s perceived physical and mental health over time. This study has carried out to find out the food insecurity, nutritional status and health related quality of life (HRQOL) of female garment factory workers and also the relationship of health related quality of life with food insecurity and nutritional status of female garment factory workers. This study has found that 71.9 percent female garment factory workers are food insecure and the percentage of being food secure is 28.1 percent. According to the Body Mass Index (BMI) classification for Asian people, 60.6 percent workers are in the normal range (17.5-22.9kg/m2), while 27.2 percent are in the overweight (23-27.9kg/m2) and 4.1 percent are in obese category (≥28 kg/m2), and 8.1 percent are underweight (